2019
DOI: 10.1186/s40104-019-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

An improved Tet-on system in microRNA overexpression and CRISPR/Cas9-mediated gene editing

Abstract: Background Tetracycline (Tet)-regulated expression system has become a widely applied tool to control gene activity. This study aimed to improve the Tet-on system with superior regulatory characteristics. Results By comprehensively comparing factors of transactivators, Tet-responsive elements (TREs), orientations of induced expression cassette, and promoters controlling the transactivator, we developed an optimal Tet-on system with enhanced inducible efficiency and lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…2 A,B). It has previously been reported that expression of rtTA-M2 by strong promoters compromises inducible expression 16 , 17 . We therefore relocated the original rtTA-M2 sequence distal to the RPBSA and downstream from either one (pSBtet-2) or two (pSBtet-3) additional GOI.…”
Section: Resultsmentioning
confidence: 99%
“…2 A,B). It has previously been reported that expression of rtTA-M2 by strong promoters compromises inducible expression 16 , 17 . We therefore relocated the original rtTA-M2 sequence distal to the RPBSA and downstream from either one (pSBtet-2) or two (pSBtet-3) additional GOI.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, much attention has been dedicated to explore the diagnostic significance of miRNAs in cancer . In 2002, Calin et al drew a relationship between cancer‐ and tissue‐derived miRNA where it was demonstrated that miRNA cluster miR 15/16 was downexpressed in chronic lymphocytic leukemia.…”
Section: Diagnostic and Prognostic Roles Of Rnamentioning
confidence: 99%
“…RT‐qPCR is a sensitive and widely used method for RNA analysis due to the advantages associated with the requirement of relatively less starting RNA, wide dynamic range, and better accuracy . Over the past several decades, a great number of RT‐qPCR‐based RNA expression analysis methods have been developed and also commonly used in clinical trials . In 2005, Chen et al developed one of the well‐known methods for miRNA analysis, referred to as TaqMan miRNA assay ( Figure I).…”
Section: Rna Biomarker Detection Technologiesmentioning
confidence: 99%
“…Here we focus on characterizing the DOX response in the renal epithelial cell line, mIMCD3. The cells have been engineered to include a tetracycline-inducible gene expression system (Schlimpert et al, 2018;Lashhab et al, 2019;Kang et al, 2019), and the model has proven popular for studying genes in a renal epithelial environment. Here we examine how DOX affects the transcriptome profiles of mIMCD3 cells with RNA-Seq.…”
mentioning
confidence: 99%